Preclinical and clinical studies of smoke-inhalation-induced acute lung injury: update on both pathogenesis and innovative therapy. (May 2019) - Guo, Bingxin; Bai, Yichun; Ma, Yana; Liu, Cong; Wang, Song; Zhao, Runzhen; Dong, Jiaxing; Ji, Hong-Long
Smoke-inhalation-induced acute lung injury (SI-ALI) is a leading cause of morbidity and mortality in victims of fire tragedies. SI-ALI contributes to an estimated 30% of burn-caused patient deaths, and recently, more attention has been paid to the specific interventions for this devastating respiratory illness. In the last decade, much progress has been made in the understanding of SI-ALI patho-mechanisms and in the development of new therapeutic strategies in both preclinical and clinical studies. This article reviews the recent progress in the treatment of SI-ALI, based on pathophysiology, thermal damage, airway obstruction, the nuclear-factor kappa-B signaling pathway, and oxidative stress. Preclinical therapeutic strategies include use of mesenchymal stem cells, hydrogen sulfide, peroxynitrite decomposition catalysts, and proton-pump inhibitors. Clinical interventions include high-frequency percussive ventilation, perfluorohexane, inhaled anticoagulants, and nebulized epinephrine. The animal model, dose, clinical application, and pharmacology of these medications are summarized. Future directions and further needs for developing innovative therapies are discussed. The reviews of this paper are available via the supplementary material section.